The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnhum.2022.912276
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Practice of Tai Chi for More Than 6 Months With Mental Health and Brain in University Students: An Exploratory Study

Abstract: To study whether Tai Chi (TC) practice can improve the brain connectivity of the prefrontal lobe of college students, the positive psychological capital questionnaires and resting EEG signals were acquired from 50 college students including 25 TC practitioners and 25 demographically matched TC healthy controls. The results showed that the score of the positive psychological capital questionnaire of the TC group was significantly higher than that of the control group, and the node degree of the frontal lobe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…A 2018 systematic review identified tai chi increases both brain connectivity and grey matter volume (57). Since that time, multiple studies have confirmed these findings in young (58)(59)(60), middle-aged (61,62), and older adults (63,64).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A 2018 systematic review identified tai chi increases both brain connectivity and grey matter volume (57). Since that time, multiple studies have confirmed these findings in young (58)(59)(60), middle-aged (61,62), and older adults (63,64).…”
Section: Introductionmentioning
confidence: 95%
“…A 2018 systematic review identified Tai Chi increases both brain connectivity and grey matter volume [63]. Since that time, multiple studies have confirmed these findings in young [64][65][66], middle-aged [67,68], and older adults [69,70]. There is preliminary evidence that Qigong may have similar effects [71,72].…”
Section: Introductionmentioning
confidence: 97%
“…However, as a multicomponent mind–body practice, TCE can not only help improve physical health but also benefit psychological health among patients with chronic disorders 23 . Studies have shown that TCE such as Tai Chi has an impact on specific brain areas of the brain, 24 and the prefrontal cortex is likely a key biomarker among the multiple complex neural correlates to help an individual manage negative mental health 25 . Previous meta results point out that Tai Chi was beneficial for ameliorating physical and mental health of patients with KOA 26 .…”
Section: Introductionmentioning
confidence: 99%